FEATURES OF THE PROGRAM-GOAL MANAGEMENT OF THE RUSSIAN ARCTIC ZONE DEVELOPMENT - Vladimir Sergeyevich Romantsov; Artem Alekseevich Lazarev (Модернизация, инновация, развитие)
In the article the issues of application of the program – goal management methodology to the development of the complex and territorially distributed systems in relation to the Russian Arctic zone are considered. The necessity of strengthening attention to the Arctic zone development, the conditions influencing the possible development management which, in its turn, are needed to consider in modification of the program and goal management mechanisms, allowing to balance the actions of a great number of participants, to combine infrastructure arrangement with the national security insurance and to consider the national interests in international cooperation are shown. Interrelations of program and goal management of the Russian Federation Arctic Zone and the innovative companies participating in the Russian Federation Arctic Zone Development Program and projects of its implementation determine a need in innovative companies involvement. The matrix of interrelations of programs and the innovative companies’ specific features is offered.